2015
DOI: 10.1055/s-0035-1568882
|View full text |Cite
|
Sign up to set email alerts
|

Does an Early and Aggressive Combined Wrapping and Dangling Procedure Affect the Clinical Outcome of Lower Extremity Free Flaps?—A Randomized Controlled Prospective Study Using Microdialysis Monitoring

Abstract: Background The ideal starting point for flap training (FT) with the combined wrapping and dangling procedure is still a question of debate. Most units follow their own established protocols and currently evidence of flap compromise due to FT is still lacking. The aim of this study was to prove if an early and "aggressive" wrapping and dangling protocol could lead to metabolic changes, measured by microdialysis, indicating ischemia resulting in compromised flap perfusion. Methods Between 2010 and 2014, 49 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Early flap compression, defined as interventions commenced within the first postoperative week, was reported in 7 studies that included a total of 253 patients. All of these used elastic bandages to achieve compression at this stage, starting as early as post-operative day 1 8,9,[14][15][16][17][18] . Out of these, 4 complete flap failures were reported, resulting in an overall flap failure rate of 1.6% for early flap compression.…”
Section: Resultsmentioning
confidence: 99%
“…Early flap compression, defined as interventions commenced within the first postoperative week, was reported in 7 studies that included a total of 253 patients. All of these used elastic bandages to achieve compression at this stage, starting as early as post-operative day 1 8,9,[14][15][16][17][18] . Out of these, 4 complete flap failures were reported, resulting in an overall flap failure rate of 1.6% for early flap compression.…”
Section: Resultsmentioning
confidence: 99%
“…A month and a half, halfway through the experiment, allowed us also to obtain important knowledge about the flow of the wound healing process and correspond it to standard clinical practice to detect early complications or address when a patient reports any inconvenience or dissatisfaction [ 24 ]. At this point in the study, no differences between first assessment and final results were reported in all groups that could be related to the rare clinical occurrence of deterioration when no early complications were detected [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jokuszies et al [4] and Neubert et al [5] performed the only two known randomized controlled trials in this patient group. They compared an early start of the dangling protocol on POD 3 to the more standard starting point on POD 7.…”
Section: Introductionmentioning
confidence: 99%
“…It must be noted that the patients included in these studies were for the most part the same group of patients. Furthermore, the numbers of patients in both studies were small (31 and 49), resulting in an underpowered study [4, 5]. McGhee et al published a systematic review comparing an early dangling protocol to a late dangling protocol [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation